Early steep decline of liver stiffness predicts histological reversal of fibrosis in chronic hepatitis B patients treated with entecavir. Issue 5 (14th February 2019) - Kong, Yuanyuan; Sun, Yameng; Zhou, Jialing; Wu, Xiaoning; Chen, Yongpeng; Piao, Hongxin; Lu, Lungen; Ding, Huiguo; Nan, Yuemin; Jiang, Wei; Xu, Youqing; Xie, Wen; et al.
Summary: It is unknown whether dynamic changes of liver stiffness measurement (LSM) can predict the reversibility of fibrosis. Therefore, we evaluated the utility of LSM changes in predicting histological changes of fibrosis in patients with chronic hepatitis B (CHB) on antiviral therapy. In a prospective cohort of CHB patients treated with entecavir, virological measurement and biochemical measurement along with LSM were measured at baseline and every 6 months. Liver biopsies were conducted at baseline and month 18 of treatment. Fibrosis regression was defined by the following two criteria: (a) Ishak score decrease ≥1 stage, (b) Ishak score decrease ≥1 stage or predominantly regressive by post‐treatment PIR classification. The dynamic changes of LSM and its predictive value for histological reversibility were evaluated with piecewise linear mixed‐effects model and ROC analysis. We found that at month 18 of antiviral therapy, liver fibrosis was reserved in 86 of 212 (40.6%) CHB patients by Ishak reversal criterion. Overall, a decline in LSM was associated with attenuation of Ishak score. The rate of LSM decline in the first 6 months was significantly faster in patients with fibrosis reversal (ΔLSM%Ishak = −2.19%/month, P = 0.0025; ΔLSM%Ishak/ PIR = −2.56%/month, P = 0.0004). The predictive model based on baseline FIB‐4 and Ishak score as well as baseline LSM, PLT, albumin and their changes during the first 6 months could predict histological reversal (AUROCIshak = 0.74, 95% CI: 0.67‐0.80; AUROCIshak/PIR = 0.81, 95% CI: 0.74‐0.87). We conclude that in CHB patients, changes in LSM during the first 6 months of entecavir therapy can predict histological reversibility of liver fibrosis at month 18 of antiviral therapy.